Setting the Agenda with an Infinite Text (Zeitschrift für Migrationsforschung, 2025)
This contribution examines the significant role of Jochen Oltmer as an agenda-setter in migration studies. It argues that Oltmer’s academic work over the last 30 years has shaped scholarly and public discourse in Germany and beyond. The analysis focuses on three key conceptual frameworks that can be traced in Oltmer’s distinctive writing mode of an »infinite text«: a) migration as a state-regulated process, b) migration regimes, and c) migration as negotiation. In addition, it assesses their impact through the lens of Andreas Wimmer’s model for analyzing influential scholars. The paper highlights Oltmer’s commitment to interdisciplinary analysis, historical depth, and contemporary relevance, emphasizing his contribution to understanding migration as a constitutive aspect of human existence.Agenda-Setting mit einem unendlichen TextDieser Beitrag untersucht die Rolle von Jochen Oltmer als Agenda-Setter in der Migrationsforschung. Er argumentiert, dass Oltmers Werk über die letzten 30 Jahre hinweg die wissenschaftliche Forschung wie auch die öffentliche Debatte über Migration geprägt hat. Die Analyse konzentriert sich auf drei in Oltmers Arbeitsmodus des »unendlichen Texts« aufscheinende konzeptionelle Perspektiven: 1) Migration als staatlich regulierter Prozess, 2) Migrationsregime und 3) Migration als Aushandlung. Ausgehend von Andreas Wimmers Modell des akademischen Agenda-Setters analysiert der Beitrag daran anschließend die Wirkung Oltmers auf die wissenschaftlichen und öffentlichen Debatten um Migration. Dabei stellt er insbesondere Oltmers Engagement für interdisziplinäre Analyse, historische Tiefe und zeitgenössische Relevanz heraus, die seinen Beitrag zum Verständnis von Migration als konstitutivem Aspekt der menschlichen Existenz auszeichnen.
Keywords: Infinite text; migration regimes; negotiation; agenda-setting in academia